2010
DOI: 10.1111/j.1365-2214.2010.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental perspectives on caring for a child with chronic kidney disease: an in‐depth interview study

Abstract: Despite facing profound and pervasive difficulties, parents strived to fulfil their dual parental and health care provider responsibilities. Parents appear to need better support structures to help them cope with the difficulties encountered during all stages of their child's illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
2
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(171 citation statements)
references
References 16 publications
(18 reference statements)
9
146
2
14
Order By: Relevance
“…13 Still, adaptation requires that the family caregiver includes all family members, so that the healthy ones don't feel neglected as described below: […”
Section: ] (E-9 )mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Still, adaptation requires that the family caregiver includes all family members, so that the healthy ones don't feel neglected as described below: […”
Section: ] (E-9 )mentioning
confidence: 99%
“…12 Similar results related to family dynamics (the home, employment, financial and leisure environment) was interrupted with the diagnosis of the child's kidney disease, since the family caregiver is most often the mother and needs to be present with the child in addition to managing care at home. 13 In this context, the experience of discovering CKD with confirmation of diagnosis needs to be observed by the nursing profession as an opportunity to approach the family in primary health care and to invest in the promotion of the adaptation to the care that will be necessary to ensure the equilibrium of the family unit.…”
mentioning
confidence: 99%
“…In a series of in-depth interviews with parents of children with CKD, Tong et al identified four major themes: absorbing the clinical environment, medicalizing parents, disruption of family norms, and the need to develop new coping strategies and support structures (22). In the study, parents consistently reported having a child with CKD as "a pervasive and profoundly negative experience."…”
Section: Children and Families With Few Social Resourcesmentioning
confidence: 99%
“…In the study, parents consistently reported having a child with CKD as "a pervasive and profoundly negative experience." (22) Other studies have noted pediatric dialysis disrupts family life (23,24), affects parental marriages (23,25,26), parental healthrelated quality of life (HRQOL) (24), parental stress (26)(27)(28)(29), and results in less parental time spent with healthy siblings (30) and more schooling problems in siblings (23). While all of these studies are limited by small sample sizes, future research may provide better guidance.…”
Section: Children and Families With Few Social Resourcesmentioning
confidence: 99%
“…[20] En este estudio, el apoyo fue proporcionado por las madres en etapa adulta, coincidiendo con Montalvo quien encontró que en mayor proporción las mujeres desempeñan este rol, [21] [22] Las características de los menores, se relacionan con los ha llazgos de Delucchi, donde la edad promedio de los niños era de 8,6 años y alta la incidencia de niños en diálisis peritoneal, la disminu ción en la edad de ingreso y el deterioro progresivo en su crecimien to requiere la presencia de un cuidador. Respecto al tratamiento, la apreciación de las cuidadoras se relaciona con lo encontrado por Tong, en este estudio se asocia con estrés, cansancio e impotencia.…”
Section: Discussionunclassified